Determination of Polyhydric Phenols in Chrysanthemum by Capillary Electrophoresis with Electrochemical Detection - Tang, Jing; Biao Zheng, Sheng; Zhu, Jin-Kun; Mei Zhang, Xue; Fei Wang, Jian (Asian Journal of Chemistry, 2013)
Chrysanthemum has been known for its accumulation of polyhydric phenol. These contents are important because of their nutritional and antioxidant properties. Two flavonoids (quercetin and luteolin) and chlorogenic acid were separated and determined in Chrysanthemum by capillary electrophoresis with electrochemistry detection (CE-ED). The effects of some important factors such as the potential applied to the working electrode, the concentration of the running buffer, separation voltage and injection time were investigated. Under the optimum conditions, the work electrode was a 300 μm diameter carbon disk electrode and the detection potential was +0.95 V (versus SCE), the analytes could be well separated within 19 min with 40 mmol L-1 Na2B4O7-H3BO3 (pH 9.2) as the running buffer. The response was linear over two orders of magnitude with detection limits (S/N = 3) ranging from 4.75 × 10-7 g mL-1 to 1.04 × 10-6 g mL-1. The method has been successfully applied for the analysis of real sample, with satisfactory results.